A simple and practical preparation of an efficient water soluble olefin metathesis catalyst1. Issue 6 (8th June 2015) - Wang, Zhen J.; Jackson, W. Roy; Robinson, Andrea J.
<x xml:space="preserve">Abstract</x> A facile gram-scale preparation of a di-ammonium functionalised Ru-alkylidene complex which efficiently catalyses ring-closing metathesis and cross-metathesis reactions in water.